Tax Planning, Deferred Tax Assets, Tax Avoidance and Earnings Management: Empirical Study on Basic Materials Sector Companies - Miranda Miranda; Imar Halimah (Journal of Management Accounting, Tax and Production, 2026)
The purpose of this study is to provide empirical evidence regarding the influence of tax planning, deferred tax assets, and tax avoidance on profit management in companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Through the purposive sampling technique, 155 observations were obtained that became research samples, which came from 31 companies that met the research criteria. In addition, this study uses a quantitative method with panel data regression analysis techniques as the analysis method. Based on the research that has been conducted, it is obtained that tax planning and deferred tax assets have an effect on profit management, while tax avoidance has no effect on profit management. The implication of this study is that companies are expected to be more careful in setting tax policies so as not to encourage opportunistic profit management practices.